THE ANALYSIS OF FACTORS AFFECTING ASSET GROWTH IN SHARIA INSURANCE COMPANIES FOR THE 2013 – 2017 PERIOD - Alien Lilavira; Siti Zulaikha (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the effect of Operational Costs, Growth in Investment Returns, Contribution and Profitability to Asset Growth in Sharia Insurance Companies in Indonesia 2013-2017. This study uses a quantitative approach. The analysis technique used is multiple linear regression analysis. This study uses 21 data samples. Data is obtained from each of the Sharia Insurance Company's Financial Reports. The results showed that the variables of operational costs, growth in investment returns, contributions and profitability have a significant effect on asset growth simultaneously in sharia insurance companies in Indonesia. The variables of growth in investment returns, contributions and profitability have a significant positive effect partially, while the operational cost variable has no significant effect.Keywords: Operating Costs, Growth in Investment Returns, Contribution, Profitability, Asset GrowthREFFERENCE Ali, Hasan AM. (2004). Asuransi dalam Perfektif Hukum Islam: Suatu Tinjauan Analisis Historis, Teoritis, & Praktis. Jakarta: Kencana.Ali, Zinuddin. (2008). Hukum Asuransi Syariah. Jakarta: Sinar Grafika.Amrin, Abdullah. (2006). Asuransi Syariah. Jakarta: Elex Media Komputindo.Anshori, Muslich dan Sri Iswati. (2009). Buku ajar metodologi peneitian kuantitatif. Surabaya: Airlangga University Press.Ansori dan Iswati. (2009). Metodologi penelitian kuantitatif. Surabaya: Airlangga University Press Ghozali, I. (2006). Analisis Multivariate dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, Imam. (2011). Aplikasi analisis multivariate dengan program IBM SPSS 19. Semarang: Badan Penerbit Universitas Diponegoro.Kasmir. (2008). Analisis laporan keuangan. Jakarta: PT Raja Grafindo Persada.Kasmir. (20140. Analisa laporan keuangan. Depok: Rajawali Pers.Kementerian Agama. (2019). Website Al-Qur’an kementerian agama. Jakarta: Kementerian Agama.Kurniawan, Robert dan Yuniarto, Budi. (2016). Analisis regresi. Jakarta: Kencana Prenada Media Group.Otoritas Jasa Keuangan. (2015). Jumlah perusahaan dan unit asuransi syariah, (Online), (http://www.ojk.go.id) PT Adira Dinamika. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.asuransiadira.com) PT AIA Financial. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.aia-financial .co.id)PT Allianz Life Indonesia. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.alamin-insurance.com)PT Astra Buana. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.asuransiastra.com)PT Asuransi Allianz Utama. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.allianz.co.id) PT Asuransi Jiwa Al-amin. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.alamin-insurance.com) PT Asuransi Takaful Keluarga. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.takaful.co.id) PT Asuransi Umum Mega. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.megainsurance.co.id) PT AXA Financial. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.axa.co.id) PT Bangun Askrida. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.askrida.com) PT Bringin Jiwa Sejahtera. (2019). Laporan Keuangan Unit Syariah, (Online), (https://www.bringinlife.co.id) PT Central Asia. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.car.co.id) PT Jiwa Manulife Indonesia. (2019). Laporan Keuangan Unit Syariah, (Online), (https://www.manulife-indonesia.com) PT Jiwa Sinarmas. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.sinarmas.co.id) PT Panin Daichi Life. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.panindai-ichilife.co.id) PT Prudential Life Assurance. (2019). Laporan Keuangan Unit Syariah, (Online), (http:www.prudential.co.id) PT Ramayana. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.ramayanainsurance.com) PT Staco Mandiri. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.stacoinsurance.com) PT Toko Marine Life Insurance. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.tokiomarine.com) PT Tugu Pratama. (2019). Laporan Keuangan Unit Syariah, (Online), (http://www.tugu.com) Ramadhani, H. (2015). Prospek dan Tantangan Perkembangan Asuransi Ssyariah di Indonesia. Jurnal Ekonomi dan Bisnis Islam, 1(1), 57-66.Salman, S. A. (2014). Countemporary Issues in Takaful (Islamic Insurance). Journal Asian Social Science, 10(22), 210-216.Sarjono, Haryadi dan Julianita, Winda. (2011). SPSS vs LISREL. Jakarta: Salemba Empat.Sastri, I. A. I.P., dkk. (2017). Pengaruh pendapatan premi, hasil investasi, dan risk based capital terhadap laba perusahaan asuransi. E-jounal Akuntansi, 7(1), 1-11.Soemitra, Andri. (2009). Bank dan Lembaga Keuangan Syariah. Jakarta: Kencana Pranada Media Group.Sugiyono. (2015). Metode penelitian kuantitatif, kualitatif, dan R & D. Bandung: Alfabeta.Suhardi & Karmawan. (2007). Konsep aset: (tinjauan statement of financial accounting concept vs standar akutansi keuangan). Journal Equity, 1(1), 7-18.Sula, Muhammad Syakir. (2004). Asuransi syariah (life and general). Jakarta: Gema Insani.Sutama, I. P., & Sastrodiharjo, I. (2015). Faktor-faktor yang mempengaruhi pertumbuhan aset perusahaan asuransi jiwa non syariah di Indonesia. Jurnal Akuntabilitas, 8(1), 18-38Yudiatmaja, F. (2013). Analisis regresi dengan menggunakan aplikasi computer stataistik SPSS. Jakarta: PT Gramedia Pustaka Utama.